Business Development Strategy of “Healthfull” Brand Products Using SWOT-AHP Analyses - Putri, Belia Berliani; Perwitasari, Sophia Dwiratna Nur; Pratopo, Lukito Hasta (Jurnal Manajemen dan Agribisnis, 2024)
In recent years, public awareness of adopting a healthy lifestyle has increased, as shown by the increase in fruit and vegetable consumption one of the business activities at PT. Hydroponics Padjadjaran Indonesia produces and sells cold-pressed juice and salad under the brand "Healthfull". “Healthfull” brand products face problems related to the number of sales. This research aims to determine alternative strategies and choose strategic priorities for the business development strategy of Healthfull brand products. Employing qualitative and quantitative research techniques, including IFE-EFE-IE, SWOT, and AHP analyses. The result of the IE matrix analysis shows that the company is in quadrant V, resulting in 8 alternative strategies formulated in the SWOT matrix, which are then analyzed using AHP to obtain strategic priorities. The results of the AHP analysis show that the strategic criteria for developing this business are increasing in sales volume (0.73) and strategic priority "increasing educational content regarding healthy food consumption through digital marketing on social media such as Instagram and Facebook" (0.163). Improving shelf life, targetting specific consumers, delivering products to store partners consistently, and providing discounts are the findings of this research. Keywords: vegetable consumption, business development strategy, healthy lifestyle, strategic priorities